Legal Certainty of Binding Power of Marriage Agreements Not Registered of Notary - Janita Wulandari; Benny Djaja; Maman Sudirman (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study discusses the legal certainty related to the binding force of marriage agreements that are not registered by a notary, by referring to the Constitutional Court Decision Number 69/PUU-XIII/2015. In this decision, notaries are given the authority to validate marriage agreements. However, agreements that are only validated by a notary without being registered with the Office of Religious Affairs or the Population and Civil Registration Service do not fulfill the principle of publicity, which is important to ensure that the document can be accessed by third parties who may be affected. Without registration, the agreement does not have binding legal force for third parties, thus potentially causing legal uncertainty and disputes in the future. The principle of publicity aims to provide protection for third parties by ensuring access to the rights and obligations stipulated in the agreement. Registration of marriage agreements at the Population and Civil Registration Service provides stronger legal certainty, maintains transparency, and protects the rights of all parties involved in accordance with applicable legal provisions.